Oral ulcers in patients treated with palbociclib: a case report - Alande Cédric; Fénélon Mathilde; Fricain Jean-Christophe (EDP Sciences, 2018)
Introduction: Palbociclib is an approved drug in the treatment of women with advanced or metastatic estrogen receptor (ER)-positive, human epidermal growth factor receptor 2 (HER2)-negative, breast cancer. The purpose of this article is to present the first case ever described of oral ulcers caused by palbociclib. Observation: A case of drug-induced oral ulcers is reported. The patient was treated with a combination of palbociclib and Fulvestrant for a breast cancer relapse with pulmonary involvement. These ulcers were localized on the ventral face of the tongue and on the gum. A therapeutic combination of infrared laser biostimulation and a topical application of Dermoval® and Dynexan® were carried out. Palbociclib was concurrently discontinued. The lesions healed in about 15 days. Comments: Palbociclib is an inhibitor of cyclin-dependent kinases 4 and 6 (CDK 4/6). Thereby, it blocks many signaling pathways responsible for cell proliferation. This property weakens the oral mucosa and could be the cause of the observed ulcers. These latter having been particularly debilitating for the patient. Conclusion: Palbociclib-related oral aphthous ulcers are similar to those reported with other targeted therapies. The combination of infrared laser biostimulation and local corticosteroid therapy did not prevent the discontinuation of the cancer treatment.